UTILITARIANISM WRITES NARRATIVES IN THE CONTENT OF PARAGRAPHS USING AESTHETIC DICTION - Asep Roni Nuriana; Alwi Kuswoyo El Luthfi; Dede Intan (JLER (Journal of Language Education Research), 2022)
This article aims to describe utilitarianism in writing narratives in conveying the hidden message to the contents of paragraphs using aesthetic diction, research conducted in SMP IT Al-Qohhariyyah with the object of research in class IX from the results of the study illustrating that 45% of students were unable to deliver the mandate using aesthetic diction caused by not having an idea of the mandate to be delivered and not knowing the aesthetic diction, 30% of students were able to convey the mandate but did not use the aesthetic diction of this group had the ideas and mandate to be delivered but did not yet know the aesthetic diction and 25% of students were able to convey the mandate the aesthetics of this group have ideas and amants to be conveyed and have known aesthetic diction. The research method used is a quantitative method with a descriptive approach.